Perceived severity of smuggling at the border of Táchira- North of Santander: Health Psychology Approach (2018)
This study analyzed the differences in the perception of severity of smuggling between consumers and smugglers of the Colombian-Venezuelan border. A correlational-comparative design was used, and the population selected was the inhabitants of North of Santander Department, Colombia, calculating a stratified randomized sampling for 2,383 people. It was found that 6% of the sample belonged to illegal traders, being mostly men. The comparison performed by sex concluded that the level of severity perceived is greater in women, and both groups gave greater relevance to the risk of losing the economic investment front others risks of more severity. The comparison by municipalities, revealed that the capital presented lower levels of perceived severity than other territories. In addition, greater perceived severity of smuggling in young adults, heads of household, married people, traders who earned less than two Colombian minimum wages and who traded individually were identified. Finally, a positive relationship was found between the level of perceived severity and conditions such as the number of products smuggled or work income.